Limites da intervenção do poder judiciário no plano de recuperação judicial: perspectivas à luz da análise econômica do direito - Rodrigues Filho, João de Oliveira (2024)
This paper seeks to demonstrate the need to expand the application of law through an economic analysis of its institutes and principles, as a way to improve the efficiency of its application in solving problems involving the institute of judicial recovery. The emergence of a business activity that lives a situation of economic and financial crisis requires a reorganization of the operation itself, based on economic premises. Its survival, in addition to the interest of the entrepreneur himself, is important because it is through private initiative that Brazilian economic activity is developed, generating social benefits, such as the generation of jobs, the production and circulation of wealth and the collection of taxes. The indiscriminate liquidation of business activities is harmful to society, since it reduces the economic poles necessary for the creation and circulation of wealth, with the consequent direct decrease in the generation of social benefits. Therefore the existence of judicial reorganization of companies, as a way to provide a chance for the survival of a business operation that lives a crisis surmountable. This overcoming depends on a plan based on economic premises to be presented in a judicial process. But the fact that the uplift occurs in a formal environment does not remove the need for a greater balance that should exist between state intervention and the market solution, so that there is greater efficiency to the institute. To this end, will be analyzed the profile of the company and free enterprise in Brazilian law, models of judicial recovery of companies from other countries, especially the United States, economic analysis of Law and the intersection of this economic analysis in several legal institutes. At the end, it will be sought to demonstrate the application of the economic analysis of the law, with evaluation of the consequences of the existing alternatives in the legality control of the recovery plan of the company, to expand the limits of hermeneutics, without disregarding the right and without underestimating the economic aspects essential for the success of the recovery.